Design to promote mindfulness practice and sense of self for vulnerable women in secure hospital services - Thieme, Anja; Wallace, Jayne; Johnson, Paula; McCarthy, John; Lindley, Siân; Wright, Peter; Olivier, Patrick; Meyer, Thomas (Proceedings of the 2013 SIGCHI conference on Human Factors in computing systems (CHI 2013), 2013)
In the field of mental health care technologies, very limited attention has been given to the design of interventions for individuals who undergo treatment for severe mental health problems in intense care contexts. Exploring novel designs to engage vulnerable psychiatric patients in therapeutic skills practice and expanding on the potential of technology to promote mental health, the paper introduces the design concept of the Spheres of Wellbeing. A set of interactive artifacts is developed specifically for women with a dual diagnosis of a Learning Disability and Borderline Personality Disorder, living in the medium secure services of a forensic hospital in the UK. The women present a difficult to treat group due to extremely challenging behaviors and a fundamental lack of motivation to engage in therapy. The Spheres are designed to assist the women in practices of mindfulness, to help them tolerate emotional distress and to strengthen their sense of self, all of which are vital components of their specialist treatment Dialectical Behavioral Therapy (DBT). The Spheres are intended to supplement the therapy of the women and to contribute to our understanding of designing technology to enhance mental wellbeing and quality of life more generally.